Lago El Rincón, Holoceno del departamento de Tafí del Valle, provincia de Tucumán (Argentina): palinología y facies sedimentarias - Garralla, Silvina Susana (2001)
Palynological and sedimentological analyses of a paleolake at El Rincón (Tafí del Valle, Tucumán; 26º 58´S, 65º 47´W) were carried out. Five sections are described with two 14 C datongs which show that the lake existed since 10,350 ± 80 to 4,120 ± 60 years B.P. Three sedimentological phaces were described which correspond to the lake history. Also, three climatic/ palynologic episodes were detected. Before 10,350 ± 80 years B.P., initial phase of the lake, a vegetation of grass steppe prevailed and the presence of characteristic elements of humid climates was recorded. Between 10,350 ± 80 and 4,120 ± 60 years B.P., the lake phase, the vegetation was represented by grass-shrub steppe and there was increase of vegetation characteristic of typical wet and aquatic environments. Since 4,120 ± 60 years B.P., lake colmatation phase, there was a prevalence of Larrea, Baccharis and Poaceae with the absence of most of the species indicators of local humid conditions